Apraxia: Definition, clinical contexts, neurobiological profiles and clinical treatments - Giulio Perrotta (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Starting from the general concept of Apraxia, the present work focuses on the clinical, neurobiological, and functional aspects of the morbid condition, suggesting a multidimensional treatment between rehabilitation exercises for lost skills and psychotherapy.